E-Justice: Towards a Strategic Use of ICT in Judicial Reform - Waleed H. MalikSource; World Bank (My University, 2016)
The globalization of the economy, social trends, and other factors present new demands on judiciaries internationally, while at the same time technological and communicational advances offer opportunities to judicial policy makers to make justice more accessible, transparent and effective. In Latin American countries, the use of information technology is now very new. However, the experience in introducing technology in justice sector institutions there has been mixed. Some have had successful applications that have helped promote the rule of law. Others, however, have invested heavily with little improvement in the performance and accessibility of judicial sector institutions. These uneven returns result from several factors and considerations. The Purpose of this paper is to explore some of these broad challenges that “policy makers” face in harnessing new technologies in developing countries and taking strategic decisions to make the justice sector more service-oriented and effective.